2020
DOI: 10.1101/2020.02.24.20027490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Normative vs. patient-specific brain connectivity in Deep Brain Stimulation

Abstract: Brain connectivity profiles seeding from deep brain stimulation (DBS) electrodes have emerged as informative tools to estimate outcome variability across DBS patients. Given the limitations of acquiring and processing patient-specific diffusion-weighted imaging data, most studies have employed normative atlases of the human connectome. To date, it remains unclear whether patient-specific connectivity information would strengthen the accuracy of such analyses. Here, we compared similarities and differences betw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 74 publications
2
39
0
Order By: Relevance
“…However, a large high‐quality functional connectivity dataset from ~2–3‐year‐old children is not currently available, and a direct test of lesion network mapping using an age‐matched connectome is not yet feasible. Nevertheless, we have thus far seen minimal impact from methodological differences in how one processes connectome data, for example, global signal regression versus other artifact removal strategies, 16,54 or using patient‐specific, age‐matched, or disease‐matched normative connectomes, 16,55–58 which is reflected here by the consistent localization of infantile spasm–related connections using data from the ABCD 9‐year‐old group connectome (n = 1,000; see Fig 4E vs Fig 4F). It is possible that our results could be improved by using a connectome better matched to the age of the TSC patients, and this is an experiment we intend to perform once such data become available and extensively processed given the significant confounds present in young child fMRI data.…”
Section: Discussionmentioning
confidence: 92%
“…However, a large high‐quality functional connectivity dataset from ~2–3‐year‐old children is not currently available, and a direct test of lesion network mapping using an age‐matched connectome is not yet feasible. Nevertheless, we have thus far seen minimal impact from methodological differences in how one processes connectome data, for example, global signal regression versus other artifact removal strategies, 16,54 or using patient‐specific, age‐matched, or disease‐matched normative connectomes, 16,55–58 which is reflected here by the consistent localization of infantile spasm–related connections using data from the ABCD 9‐year‐old group connectome (n = 1,000; see Fig 4E vs Fig 4F). It is possible that our results could be improved by using a connectome better matched to the age of the TSC patients, and this is an experiment we intend to perform once such data become available and extensively processed given the significant confounds present in young child fMRI data.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, groups have begun to directly compare results using patient-specific vs. normative connectomes in DBS ( Wang et al, 2020 ) or TMS ( Cash et al, 2019 ). Both studies found no significant difference between the two connectomes in their ability to predict clinical outcomes, but noted a slight trend towards better prediction with individualized data.…”
Section: Eight Opportunities Of Connectomic Neuromodulationmentioning
confidence: 99%
“…In addition, there are inaccuracies due to the normalization process since individual anatomical variations of the tract cannot be taken into account. There is some published evidence showing that connectivity profiles for DBS drawn from normative connectomes versus patient‐based connectivity profiles were comparable in respect to brain areas that are associated with clinical improvement (22). However, the spatial normalization of brains with structural deformities (such as often the brains from HT patients) into brain atlases, remains challenging.…”
Section: Discussionmentioning
confidence: 99%